Thermal performance and corrosion resistance analysis of inorganic eutectic phase change material with one dimensional carbon nanomaterial - Kalidasan, B.; Pandey, A. K.; Saidur, R.; Mishra, Yogeshwar Nath; Ma, Zhenjun; Tyagi, V. V. (Journal of Molecular Liquids, 2023)
The inherent thermal characteristics, supercooling phenomenon, and corrosion issues associated with salt hydrate phase change materials (PCMs) limit their practical applications. In this research work, we report a newly formulated eutectic salt hydrate PCM using a) sodium sulphate decahydrate (SSD) & b) sodium phosphate dibasic dodecahydrate (SPDD); with a focus on customizing its properties to enhance its suitability for low temperature thermal regulation (achieving a melting point of 27.8 °C and a high heat storage capacity of 215 J/g). Additionally, we have successfully reduced the degree of supercooling and introduced corrosion resistant properties to this PCM. To enhance both the thermal energy transfer rate and optical absorbance of the eutectic PCM, we have incorporated one-dimensional (1D) multiwall carbon nanotube (MWCNT) at various weight fractions, extending up to 0.9 %, utilizing a two-step method. The dispersion and chemical stability of SSD/SPDD + MWCNT nanocomposite are verified through the morphological visual and spectral peaks obtained in Fourier transfer infrared spectroscopy. Additionally, studies evaluating the optical and thermal property reveal a substantial 500 % increase in absorbance, a notable 77.9 % reduction in transmissibility, a thermal conductivity increase from 0.464 W/m⋅K to 0.742 W/m⋅K (reflecting a 59.9 % increment), and the retention of a consistent melting enthalpy of 218.6 J/g. This stability is attributed to the intermolecular interaction with MWCNT. Similary, the degree of supercooling (ΔTs) for the SSD/SPDD EPCM containing MWCNT decreased to 2.2 °C from 16.5 °C, marking an 86 % reduction compared to the pure eutectic salt solution. Furthermore, this composite demonstrated enhanced thermal and chemical stability throughout 200 thermal cycles. Auxiliary ANSYS simulation, with transient boundary condition, are provided to analyze the heat transfer interactions between the thermic fluid and the newly developed PCM when integrated into a thermal regulation system. Subsequently, a corrosion analysis of the developed eutectic PCM and the nanocomposite eutectic PCM exhibits a corrosion rate of 0.018 mpy, well below the permissible level (<5mpy). The insights gained from the development of this nanocomposite PCM offer valuable guidance for the design and creation of tailored eutectic PCM for low-temperature thermal regulation systems, resulting in significant energy savings.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Eutectic Phase Change Material; Multi-wall CNT; Salt hydrate; Thermal Energy Storage; Thermal stability